Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T15:39:16+01:00
A)3(a-2)= 3a-6
b)-4(x+y)= -4x-4y
c)-5(-x=1)= 5x-5
d)-3a(jedna trzecia - a)= -3/3a+3a²
e)(t-2s-1)razy 7= 7t-14st-7
f)jedna druga (2a-4b+1)= a-2b+1/2
g)m(2m+3)= 2m²+3m
h)3p(2r+5p-1)= 6pr+15p²-3p
i)xy(2x-3y+5)= 2x²y-3xy²+5xy
2010-02-04T15:39:57+01:00
A)3(a-2)= 3a-6
b)-4(x+y)= -4x-4y
c)-5(-x=1)= 5x-5
d)-3a(jedna trzecia - a)= -3/3a+3a²
e)(t-2s-1)razy 7= 7t-14st-7
f)jedna druga (2a-4b+1)= a-2b+1/2
g)m(2m+3)= 2m²+3m
h)3p(2r+5p-1)= 6pr+15p²-3p
i)xy(2x-3y+5)= 2x²y-3xy²+5xy
2010-02-04T15:40:49+01:00
A)3(a-2)= 3a-6
b)-4(x+y)= -4x-4y
c)-5(-x+1)= 5x-1
d)-3a(jedna trzecia - a)= -a+3a²
e)(t-2s-1)razy 7= 7t-14s-7
f)jedna druga (2a-4b+1)= a-2b+1/2
g)m(2m+3)= 2m²+3m
h)3p(2r+5p-1)= 6pr+15p²-3p
i)xy(2x-3y+5)= 2x²y-3xy²+5xy